PERANCANGAN SISTEM INFORMASI PEMESANAN WEDDING ORGANIZER DI KOTA PADANG - Dwika Permata; Elfi Tasrif; Ika Parma Dewi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2018)
Wedding Organizer is a service that works personally to help bride and groom in planning and supervision of the implementation of the wedding party in accordance with schedule and bugdet that have been set. Wedding organizer information system created using web-based information technology, with the aim to expand the area of promotion and sale of wedding packages and simplify the ordering process. System Design Information Ordering Wedding Organizer is UML modeling visualization (Unified Modeling Language) by using some object-oriented visualization diagram. The programming language used is the PHP programming language (PHP Hypertext Preprocessor) based on the Laravel framework as well as Javascript, with MySQL as the Database Management System (DBMS), and Atom as an editor. Wedding organizer information system is very helpful for people who do not want to bother with their wedding planning issues. With the development of technology today, wedding Organizer has begun to move from the manual process into the online process of wedding information system-based organizer web.Keywords: Information System, booking Wedding Organizer, web, Laravel